2011
DOI: 10.1002/bse.672
|View full text |Cite
|
Sign up to set email alerts
|

Evidence in development of sustainability reporting: a case of a developing country

Abstract: Current development in social accounting presents an interesting phenomenon. Companies are increasingly engaging in sustainability initiatives and reporting their activities in annual reports, company websites and other media of communication. Unlike previous studies, which have mainly used ex post content analysis of annual reports or other published data to study the relationship between disclosure and possible determinants, this study starts with an interview with the local preparer before the data is trian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
217
3
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 226 publications
(239 citation statements)
references
References 56 publications
13
217
3
6
Order By: Relevance
“…This finding differs greatly from studies which have identified mimetic pressures often superseding normative and coercive pressures on MNE CSR practices (Amran and Haniffa, 2011).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding differs greatly from studies which have identified mimetic pressures often superseding normative and coercive pressures on MNE CSR practices (Amran and Haniffa, 2011).…”
Section: Discussioncontrasting
confidence: 99%
“…In countries such as Sri Lanka, where the state control and power has been increasing steadily, these pressures may very well arise mostly from the central government itself (Zhao, 2012;Yang and Rivers, 2009), as coercive pressures. MNEs' subsidiaries are also likely to face normative pressures, specifically those arising from professional and industrial bodies, compelling them to engage in CSR practices (Amran and Haniffa, 2011).…”
Section: The Research Framework For the Studymentioning
confidence: 99%
“…Institutional change takes place along three mechanisms: mimetic, coercive, and normative isomorphism. These three mechanisms push companies to be more transparent, and socially and environmentally responsible [48]. Mimetic isomorphism describes the process by which organisations emulate the structures and procedures adopted by other organisations [47].…”
Section: Theoretical Approachmentioning
confidence: 99%
“…In their study of six banks' CSR reports, from four countries over a period of -2011, Jain et al, (2015 found that the reporting standards have improved despite CSR reporting being a voluntary undertaking. Also based on categorising of 'themes' reported, Vilar and Simao (2015) found that there are recurring 'themes', such as 'workers' welfare' and 'corporate ethics'' being reported across the regions that were studied.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Specifically, it examines the reporting of indirect social and environmental impacts of New Zealand financial services institutions (NZFSIs), using content analysis of their voluntarily produced CSR reports, and some insights from CSR reporters and expert stakeholders. Unlike most previous studies that focussed on motivations for CSR reporting and or endeavours (e.g., Bowen, 2000;Cormier et al, 2004;O'Donovan, 2002;Amran and Haniffa, 2011;Brammer and Pavelin, 2008;Jain et al, 2015;Lock and Seele, 2015), this study looks at the extent of reporting on indirect CSR impacts, and motivation for selection of reported issues in the CSR reports. Specifically, it investigates the extent of FSIs' CSR reporting on FSIs' social and environmental impacts resultant from their core business products/services, compared to those due to non-core business products/services.…”
Section: Introductionmentioning
confidence: 99%